Thursday

April 24, 2014

April 24, 2014

Posted by **brittney** on Wednesday, November 14, 2012 at 6:58pm.

- math -
**Ms. Sue**, Wednesday, November 14, 2012 at 7:03pm-6+5x=8x-9

-6 + 9 = 8x - 5x

3 = 3x

1 = x

**Related Questions**

algbra - i was wondering what did i do wrong in this 10. Divide (3x – 2)(x - 4...

math - f(x)= 5x^2+8x+7/x^1/2 i have to find the derivative and when I do this is...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 5x...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 ...

Math(Please check) - Divide 5x^4 - 3x^2 + 8x + 6 by x^2 + 8 My answer was 5x^2...

Math - Can someone please check my answers below for accurateness? The ...

Algebra II - Assume that no denomenator equals 0. (7x^2+3x-9)-(-x^2+8x-3) = 7x^2...

math - I am doing something wrong when I work this question. Can someone show me...

algerbra 1 - 5x+8+3x-x+5=6x-3 do I start like this 5x+3x-x or 5x+3x+8+5=6x-3 I ...

Math - Factor each expression. Please show me how to do it. Thanx 8x^2-10x+3 15X...